PENERAPAN MODEL DOUBLE LOOP PROBLEM SOLVING BERBANTUAN INFOGRAFIS DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI - Chika Rahayu Wulan Jati; Euis Eti Rohaeti; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Improving the ability to write explanatory texts has become one of the important focuses in learning, as this skill trains students to convey factual information logically, systematically, and according to language rules. This study aims to understand the process of implementing the Double Loop Problem Solving (DLPS) learning model assisted by infographic media, to identify challenges for students, and to analyze the effectiveness based on improvements in writing skills and student learning outcomes. The method used is a mix method with an exploratory sequential design. The subjects of this research are 11th-grade students at a high school that implements an independent curriculum. Data collection techniques include observation, questionnaires, pre-tests, and post-tests. The results of the study show that the DLPS model assisted by infographic media can facilitate students in understanding the material through a reflective thinking process, effectively increase student engagement, and be able to stimulate students' interest in learning through more interesting and meaningful learning presentations. Observations indicate a 100% implementation of teacher learning and a 90% student involvement. The obstacles faced are minimal with an average low score of 3,11 in sentence construction in the explanatory text after evaluation. The N-gain calculation shows an increase of 0,72 with a 'High' category and student learning completeness reaches 100%. This finding reinforces that the model and media are effectively applied in problem-based writing learning in depth.